Effect of Storage Temperature on Bond Strength of a Self-Etch Adhesive System to Pulp Chamber Dentin - Donmez, Nazmiye; Ari, Hale; Belli, Sema (European Journal of Dentistry, 2009)
Objectives: The aim of this study was to evaluate the effect of storage temperature on bond strength of a self etching primer system to pulp chamber dentin.Methods: SE Bond (Kuraray, JAPAN) adhesive system and Clearfil Photo Posterior (Kuraray, JAPAN) composite resin were used. Eight extracted caries-free human molar teeth were used. Access cavities were prepared through the pulp chamber, randomly distributed into 4 groups and prepared as follows: Group 1 (Control): SE Primer and SE Bond (SEB) were applied to the pulp chamber dentin according to the manufacturer’s instructions, immediately after the delivery from the manufacturer and then the pulp chamber was restored with a resin restorative material. The primer agent of the following groups was stored in a refrigerator and kept at 4C. Group 2: restored with SEB, kept at 4°C refrigerator for 1 year, Group 3: restored with SEB kept at 23°C room temperature for 1 year and Group 4: restored with SEB kept at 40°C incubator for 1 year. After 24 hrs the teeth were trimmed for microtensile bond testing and loaded to failure at 1mm/min. Data were analyzed using one-way ANOVA and Duncan test (P<.05).Results: The results indicated that Group 4 showed lowest bond strength when compared to the others (P<.05). No statistically significant difference was found among the other groups (P>.05).Conclusions: As a result of this study, it was concluded that increasing storing temperature or storing period decreases microtensile bond strength of a SEB system to pulp chamber dentin. (Eur J Dent 2009;3:314-317)
Keywords: Storage temperature; Storage period; Bond strength; Self-etch adhesive; Chemical degradation of the adhesive